A Familial Case of Saethre-Chotzen Syndrome in Japan. Issue 1 (February 2016) - Mitsukawa, Nobuyuki; Hayashi, Takashi; Satoh, Kaneshige
Abstract : Saethre-Chotzen syndrome is extremely rare in Japan. We experienced a familial case of Saethre-Chotzen syndrome in 4 individuals of 3 generations. In all 4 individuals, a mutation in the TWIST gene was observed by a gene test. Some of these patients underwent surgical correction of brachycephaly and blepharoptosis with good results.